Aplikasi e-Posyandu Kesehatan (ePoK) Berbasis Android sebagai Alternatif Posyandu di Era New Normal - melly damayanti; Nurul Aini Suria Saputri; Nur Cahya Rachmawati (LPPM Hang Tuah Pekanbaru, 2022)
COVID-19 has been declared a world pandemic, causing child health services in several places to not run optimally, including monitoring activities at posyandu. For this reason, researchers are interested in designing an application that can be used as an alternative to monitoring the growth and development of toddlers for mothers who cannot attend the posyandu, either due to the COVID-19 pandemic or other reasons. This study aims to determine the satisfaction of using the Android-based e-Posyandu Health Application (ePoK) as an alternative to posyandu in the new normal era. This study used a quasi-experimental study on 152 mothers of children under five who were taken by proportional stratified random sampling. Mother was given the application and used it for 1 month. The data obtained were analyzed by univariate and bivariate using chi square test. Based on the results of the study, most of the respondents were aged 20-40 years (98%), the majority had high education (59.9%), most were housewives (65.8%), the number of children in general was more than one (77.6 %), and the average age is less than 2 years (84.2%). The category of respondents' satisfaction with the ePoK application is mostly in the very satisfied category, which is 88.2%. There is a relationship between the characteristics of the mother's work, parity and the age of the youngest child on the satisfaction of using the ePoK application with pvalue<0.05. Respondents were very satisfied with this ePoK application. Based on these results, it is hoped that mothers of toddlers can take advantage of the ePoK application to monitor the growth and development of their toddlers